ChemInform Abstract: Visible‐Light‐Mediated Nucleophilic Addition of an α‐Aminoalkyl Radical to Isocyanate or Isothiocyanate. Issue 14 (8th April 2014) - Zhou, Hongxia; Lu, Ping; Gu, Xiangyong; Li, Pixu
Abstract A visible‐light photoredox synthesis of α‐amino amides or α‐amino thioamides from N, N‐dimethylaniline derivatives and aryl isocyanates or aryl isothiocyanates is developed.